Stargardt disease – what general ophthalmologists should know about this macular dystrophy - Lubiński, Wojciech; Lachowicz, Ewelina (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
On the basis of the available literature in the PubMed database, we describe the pathogenesis, diagnosis and therapeutic trials in Stargardt disease (STGD). STGD is the most commonly inherited cause of visual loss in childhood and adulthood. STGD is mostly inherited in an autosomal recessive pattern and is most commonly caused by mutations in the ABCA4 gene leading to accumulation of the lipofuscin-like substance A2E, toxic to retinal pigment epithelium (RPE) and photoreceptors. Genetic analysis is necessary for a reliable diagnosis. STGD can be classified into 3 types with different prognoses based on the flash electroretinogram (ERG) and fundus autofluorescence (FAF). Spectral domain optical coherence tomography (SD-OCT), multifocal ERG (mfERG) and pattern ERG (PERG) are useful in the early detection of changes. Adaptive optics scanning laser ophthalmoscopy (AOSLO) may be used to evaluate progression and for selection of patients for clinical trials. At present, there are clinical trials: gene replacement therapy (StarGen), subretinal injection of RPE cells, oral substitutes reducing the accumulation of A2E (Alkeus, Acucella), and intravitreal injection of a drug that inhibits the complement system (Zimura). Significant progress is observed in identifying this condition at an early stage, determining clinical features, prognosis, molecular diagnostics and in understanding the pathogenesis of this disease. We are awaiting long-term results of the clinical trials.